A DON CELSO FURTADO, A SUS OCHENTA AÑOS. LA SOCIOLOGIA ECONÓMICA POSDESARROLLISTA DE CELSO FURTADO (Revista de História Regional, 2007)
This article describes and highlights some of the theoretical and politcal factes of the vast intellectual work and life of Celso Furtado. It shows how the theoretical creation and its vicissitudes are part of the life of any intellectual commited with with the politcal and economic change, but not under his control. It includes the years following the military coup of 1964, his exile from Brazil and the loss of his political rights. The author shows that the radical changes en his theoretical and political reflection can be described as a rupture from certain issues concerning economic development that had previously dominated his work and whose discursive legacy is known as dependency theory. It marked the beginning of a new theoretical, existencial era, and political, for both Furtado and Brazil.